Enzymatic formation of a meta-stable supramolecular hydrogel for 3D cell culture. Issue 39 (1st April 2015) - Chen, Guoqin; Chen, Jiaxin; Liu, Qicai; Ou, Caiwen; Gao, Jie
Abstract : A meta-stable supramolecular hydrogel triggered by phosphatase allows separation of cells post culture by simply pipetting and centrifugation. Abstract : We report the phosphatase-triggered formation of a meta-stable peptide-based supramolecular hydrogel that can easily change to a clear solution by mechanical forces. Cells cultured in the hydrogel can therefore be separated by pipetting followed by centrifugation.